Gerakan 5000 Donasi Buku Dalam Upaya Membangun Budaya Literasi : Tahap 4 - Vidila Rosalina; Donny Fernando; Saefudin Saefudin; Hikmatullah Hikmatullah (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
The society of a nation has a vertical relationship to the quality of the nation. The high interest in reading someone's book influences one's insight, mentality, and behavior. The Indonesian nation is a nation with a low literacy level even though it has been 70 years since Indonesia became an independent country. There are many factors why Indonesian society's literacy has a low percentage. These problems must immediately get serious attention not only from the government but from all of us. How does the discourse about " interest in reading " be carried out for all people when we still have a limited number of books read? So the book donation movement is in an effort to build a culture of literacy and literacy in Indonesia and in Banten in particular. When the state of literacy becomes a culture in Indonesia, it is not impossible that our nation will be an advanced nation.